PSYCHO-SOCIAL ROLES OF SPORTS AS PREDICTORS OF PEACE AND DEVELOPMENT AMONG MALE IN-SCHOOL ADOLESCENTS IN THE NIGER-DELTA COMMUNITIES IN NIGERIA (2013)
The capital infusion of government funding and philanthropic support for schools in the Niger-Delta communities has sparked off reforms which include restoring efficiency in poorly managed schools and thus, fostering peace and development in the schools. Despite these, the school system in the state is confronted with social barriers which have resulted in male in-school adolescents' ethnic intolerance. Studies undertaken to address violence in the Niger-Delta have focused on the upper echelon of government to the exclusion of the adolescents' problems and the role of sports in character building and social control.This study, therefore examined psycho-social roles of sports as predictors of peace and development among male in-school adolescents in the Niger-Delta communities of Nigeria with respect to social control, character building, occupation mobility, ethical value, group dynamics, nationalism, socialisation and youth positive restiveness. Using survey research design,this study adopted structural functionalism theory. One thousand seven hundred male in-school adolescents were selected through a multistage random sampling technique. They were drawn from Bayelsa, Delta and Rivers states in the Niger-Delta. Two instruments were used: Psycho-Sociological Roles of Sports Questionnaire (r = 0.88) and Sports for Peace and Development Questionnaire(r=0.76).These was complemented with three sessions of Focus Group Discussion (FGDs) with the male in-school adolescents.Two research questions were answered and six hypotheses tested at 0.05 level of significance. Data were analysed using multiple regression and qualitative data was subjected to content analysis. Psycho-social sport role variables jointly predicted peace and development in the selected Niger Delta communities F (8, 1691) = 67.146; p<0.05, and they contributed 24% of the variance of the dependent variable. The order of the relative contributions of the psycho-social sport roles to peace and development was as follows:social control (?=.33, p<0.05), occupational mobility (?=.24, p<0.05), character building (?=.22, p<0.05),ethical value (?=.22, p<0.05) nationalism (?=.19, p<0.05), youth positive restiveness (?=.12, p<0.05) and socialisation (?=.07, p<0.05) respectively. These implied that social control was the most potent role played by sport for peace and development in the studied communities. Sports provide socially rich environment that afforded students with many opportunities to interact with others in ways that have moral import to nurture and practice capacities for role taking, empathy, conflict resolution and various sub-skills related to moral judgment. About 70% male students from the communities in Bayelsa believed that sport roles promote moral reasoning for peace and development, while students from Rivers and Delta communities agreed that psychosocial sport roles helped to curb youth restiveness. Psycho-social sport role variables positively predicted peace and development in the selected communities in the Niger-Delta region. Therefore, socialisation through sports, ethical value, character building and social control variables that could strengthen positive behaviour of students to enhance peace and development should be pursued in all ramifications.